Palladium‐Nanoparticle‐Linked Organic Frameworks: Heterogeneous Recyclable Catalysts in Aqueous Medium. Issue 6 (21st May 2014) - Prakash, Sadasivan P.; Gopidas, Karical R.
Abstract 4, 4′‐Biphenylene‐bisdiazonium tetrafluoroborate and a palladium salt were reduced simultaneously to result in the formation of palladium atoms and 4, 4′‐biphenylene biradicals. The palladium atoms underwent clustering forming palladium nanoparticles, whereas the 4, 4′‐biphenylene biradicals underwent rapid addition reactions to other radicals and also to nanoparticle surfaces. The resulting product contains palladium nanoparticles covalently linked to an organic framework (PNOF). The effects of different reaction conditions upon metal content as well as on the morphology of the PNOF were studied. The PNOF structure was probed by different experimental techniques. The PNOFs were evaluated as heterogeneous recyclable catalyst in aqueous medium for reduction of 4‐nitrophenol and Suzuki coupling reactions. The catalyst exhibited high reactivity even in Suzuki couplings of aryl chlorides.